Expensive Ornaments or Essential Technology? A Qualitative Metasynthesis to Identify Lessons From User Experiences of Wearable Devices and Smart Technology in Health Care - Sandham M; Reed K; Cowperthwait L; Dawson A; Jarden R (y Elsevier Inc on behalf of Mayo Foundation for Medical Education and Research, 2023)
This review sought to describe experiences of using wearable devices worn on the body for the purpose of tracking health status and movement and or using in-home health-related smart technologies. In this qualitative metasynthesis, five databases were searched from database inception to May 11, 2022. Included were qualitative studies of the experiences of using wearable or in-home sensors for monitoring health. The primary outcome was any study that reported experiences of using smart health technology using a wearable device or sensors in the home. Eighteen studies covering a range of technologies and health user groups were critically appraised, and data were extracted. Primary study themes were synthesized, and participant quotes across the studies were organized to construct broad themes and subthemes. The three themes included the following: technology as a motivator; reassurance from technology; and animosity toward technology. Technology was welcomed when participants experienced benefits such as reassurance that their health was being tracked and they were aware when problems arose. Participants appreciated the technology could motivate them to challenge themselves on the basis of feedback from the device. Some participants appeared to wish to avoid the technology but experienced resentment when they could not conceal the technology and still receive the other benefits. Data collected should be accessible to the technology user and the clinician together, to enhance transparency and reduce the power differential. Trial Registration: PROSPERO Identifier: CRD42022325402